2017
DOI: 10.1007/s11695-017-2733-3
|View full text |Cite
|
Sign up to set email alerts
|

Gross Olfaction Before and After Laparoscopic Gastric Bypass

Abstract: Laparoscopic gastric bypass improves the olfaction scores of the Pocket Smell Test in morbidly obese patients 6 months after their procedure. More complex tests can be used in candidates to bariatric surgery if low scores are detected initially. Other causes of olfaction dysfunctions should be determined if there is no improvement after weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Two previous studies have tested for effects of gastric bypass on odour identification abilities but produced contrasting results. The former study observed significant improvements at 6‐month postsurgery, whereas the latter found no difference . Authors of the latter study therefore hypothesized that olfactory dysfunction was a cause rather than a consequence of obesity.…”
Section: Resultsmentioning
confidence: 99%
“…Two previous studies have tested for effects of gastric bypass on odour identification abilities but produced contrasting results. The former study observed significant improvements at 6‐month postsurgery, whereas the latter found no difference . Authors of the latter study therefore hypothesized that olfactory dysfunction was a cause rather than a consequence of obesity.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Melis et al [ 22 ] observed improved smell identification scores following different bariatric procedures (including SG, RYGB or mini gastric by-pass). However, these results [ 6 , 21 , 22 ] are not strictly comparable with each other as they use different identification tests in their studies (cross cultural smell identification test, the pocket smell test, or S’S). The improvement in the olfactory threshold in our study may have been influenced by the low number of subjects included.…”
Section: Discussionmentioning
confidence: 95%
“…Although two previous studies confirmed an improvement in the total TDI score in patients undergoing SG [ 7 , 8 ], Holinski et al [ 7 ] observed that this was mainly due to an improvement in odor discrimination, while Hanci et al [ 8 ] found a significant improvement in all the three sub-test scores. Richardson et al [ 21 ] and Zerrweck et al [ 6 ] studied smell identification before and after gastric bypass but reached opposite conclusions. More recently, Melis et al [ 22 ] observed improved smell identification scores following different bariatric procedures (including SG, RYGB or mini gastric by-pass).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In sheep, a strict nutritional intervention before mating had long-term benefits on offspring weight gain but deleterious effects on offspring stress response and glucose metabolism [35,36]. WL following bariatric surgery in humans [37,38,39], or diet reversal in rodents [5], showed mixed results on olfactory performance, suggesting that alterations to olfaction are difficult to reverse.…”
Section: Introductionmentioning
confidence: 99%